2023
DOI: 10.3390/molecules29010144
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Gaseous Benzene Using Cu/Fe-Doped TiO2 Nanocatalysts under Visible Light

Tao Tian,
Jie Zhang,
Lijiang Tian
et al.

Abstract: Visible-light-enhanced TiO2 nanocatalysts doped with Cu and Fe were synthesized using the sol–gel method to investigate their performance in degrading gaseous benzene. The structure and morphology of mono- and co-doped TiO2 (i.e., Cu/Fe-TiO2, Cu-Fe-TiO2) were characterized using SEM, EDS, XRD, BET, Raman, UV-vis-DRS, and XPS techniques. The results indicated that the presence of Cu/Fe mono- and co-doped TiO2 leads to the formation of an anatase phase similar to pure TiO2. Furthermore, the introduction of Cu/Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the literature, the range of light absorption of the catalyst could be extended by introducing other metal ions [ 15 ]. In addition, it has been reported that doping with elements such as Zn 2+ , Bi 3+ , Fe 3+ , Ni 2+ , and Cu 2+ can increase photocatalytic activity owing to enhanced electron exchange rates and a reduced band gap [ 16 , 17 , 18 ]. For instance, Zn doping enhances the charge separation and the utilization of visible light, and changes band gaps; therefore, porous Zn doped Zr 3+ -ZrO 2 composite showed excellent photocatalytic activity for tetracycline degradation due to its narrow band gaps and broaden visible light [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the range of light absorption of the catalyst could be extended by introducing other metal ions [ 15 ]. In addition, it has been reported that doping with elements such as Zn 2+ , Bi 3+ , Fe 3+ , Ni 2+ , and Cu 2+ can increase photocatalytic activity owing to enhanced electron exchange rates and a reduced band gap [ 16 , 17 , 18 ]. For instance, Zn doping enhances the charge separation and the utilization of visible light, and changes band gaps; therefore, porous Zn doped Zr 3+ -ZrO 2 composite showed excellent photocatalytic activity for tetracycline degradation due to its narrow band gaps and broaden visible light [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Cu- and Fe-doped TiO 2 nanocatalysts reveal more lattice defects and a higher concentration of surface-bound hydroxyl groups/chemically adsorbed oxygen. Consequently, Cu-Fe-TiO 2 composite has demonstrated significant photocatalytic activity, which can be attributed to its reduced band gap [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2+ doping improved the wave absorption performance. Tian et al 28 synthesized Cu- and Fe-doped TiO 2 using the sol–gel method, demonstrating that the introduction of Cu and Fe increased the presence of lattice defects and the specific surface area of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%